2018
DOI: 10.1128/mbio.02217-17
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of HDAC5 by Viral Interferon Regulatory Factor 3 Plays an Essential Role in Kaposi's Sarcoma-Associated Herpesvirus-Induced Lymphangiogenesis

Abstract: Kaposi’s sarcoma-associated herpesvirus (KSHV) is the etiologic agent for Kaposi’s sarcoma (KS), which is one of the most common HIV-associated neoplasms. The endothelium is the thin layer of squamous cells where vascular blood endothelial cells (BECs) line the interior surface of blood vessels and lymphatic endothelial cells (LECs) are in direct contact with lymphatic vessels. The KS lesions contain a prominent compartment of neoplastic spindle morphology cells that are closely related to LECs. Furthermore, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…As shown inFigure 5C, oroxylin A treatment significantly elevated the level of ubiquitinational Prox1 in the vIL-6expressing endothelial cells, which were pretreated with MG132, a specific inhibitor of the proteasome. In sum, these results reveal that interaction by PPARγ facilitates Prox1 to undergo ubiquitinational degradation.4 | DISCUSSIONLymphatic reprogramming plays a pivotal role in KS development [24][25][26]. In the present study, we successfully established a lymphatic-phenotype endothelial cell line by transduction of KSHV vIL-6 gene into the HUVECs.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…As shown inFigure 5C, oroxylin A treatment significantly elevated the level of ubiquitinational Prox1 in the vIL-6expressing endothelial cells, which were pretreated with MG132, a specific inhibitor of the proteasome. In sum, these results reveal that interaction by PPARγ facilitates Prox1 to undergo ubiquitinational degradation.4 | DISCUSSIONLymphatic reprogramming plays a pivotal role in KS development [24][25][26]. In the present study, we successfully established a lymphatic-phenotype endothelial cell line by transduction of KSHV vIL-6 gene into the HUVECs.…”
mentioning
confidence: 59%
“…Lymphatic reprogramming plays a pivotal role in KS development . In the present study, we successfully established a lymphatic‐phenotype endothelial cell line by transduction of KSHV vIL‐6 gene into the HUVECs.…”
Section: Discussionmentioning
confidence: 93%
“…No specific SIRT6 inhibitor (small compound) is available; the SIRT6-KSHV DNA might be an effective target for developing an interfering molecule for infection prevention or therapeutic purposes. Interestingly, a recent study found that the KSHV-encoded protein viral interferon regulatory factor 3, which interacts with HDAC5, contributes to KSHV-induced lymphangiogenesis, which is related to KSHV-caused malignancy (35). Therefore, studies on the relationship between HDAC/SIRT and KSHV might also result in an understanding of how KSHV causes cancer.…”
Section: Discussionmentioning
confidence: 99%
“…KSHV oncogenesis is, in part, attributed to genes expressed during latency. Viral FLICE inhibitory protein (vFLIP or K13), is a latently expressed gene that was originally identified as an inhibitor of apoptosis, due to the presence of tandem death effector domains 8,9 . vFLIP is a potent activator of NFκB signaling and this activity is dependent on interaction with IKKߛ 10-12 . vFLIP has also been shown to promote NFκB signaling through upregulation of IKKߝ and CADM1 and inhibition of the SAP18/HDAC1 complex resulting in activation of NFκB via acetylation of p65 [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%